ACTIVATION AND DIFFERENTIATION OF PERIPHERAL BLOOD MONOCYTES IN PERIODONTITIS - L. M. Tebloeva; O. A. Guseva; S. V. Philippov; S. V. Khaidukov (Медицинская иммунология, 2014)
Periodontitis is a chronic infectious inflammatory disease, being the most common bone disease in humans. Porphyromonas gingivalis bacteria are quite common in periodontal lesions, thus considered among major causal agents of periodontitis. Monocytes play a crucial role in development of the infectious events and subsequent inflammation. The aim of this study was to investigate appropriate changes of the monocyte subpopulations, as well as to assess relationships between expression of CD14, CD16, CD45RA, HLA-DR on the monocyte surfaces in the patients with periodontitis. It was demonstrated that periodontitis is accompanied by increased counts of pro-inflammatory monocytes. These changes are characterized by decreased expression of CD14, along with occurence of CD16 marker. Concomitant activation of the monocytes is reflected by CD45RA expression. However, in spite of significant increase in CD14lowCD16+HLA-DR+ cell counts observed in patients with periodontitis, these monocyte populations are not likely to play a significant role in development of a specific immune response and suppression of periodontitis.